2020
DOI: 10.1038/s41419-020-2485-1
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA KCNQ1OT1 sponges miR-34c-5p to promote osteosarcoma growth via ALDOA enhanced aerobic glycolysis

Abstract: Metabolic switch from oxidative phosphorylation to aerobic glycolysis, which is also called the Warburg effect, is a hallmark of osteosarcoma (OS) and leads to the enhancement of cell chemoresistance, growth, metastasis, and invasion. Emerging evidence indicates that long non-coding RNA (lncRNA) plays a crucial role in the Warburg effect of cancer cells. Here, we report that lncRNA KCNQ1OT1 was upregulated in OS. Meanwhile, functional experiments demonstrated that the KCNQ1OT1 facilitated proliferation and sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
95
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 43 publications
1
95
0
Order By: Relevance
“…Similarly, we found that KCNQ1OT1 promoted the proliferation, cloning, migration, and invasion of cancer cells. In addition, the knockdown of KCNQ1OT1 has been reported to significantly induce the apoptosis of osteosarcoma cells (28) and nonsmall cell lung cancer cells (20), while the silencing of KCNQ1OT1 was shown to impede methotrexate-resistant colorectal cancer cell tumor growth in nude mice (22). In vivo, we discovered that the downregulation of KCNQ1OT1 repressed the volume growth and reduced the weight of the tumors, indicating that KCNQ1OT1 may acts as a carcinogenic and chemo-resistant biomarker for SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we found that KCNQ1OT1 promoted the proliferation, cloning, migration, and invasion of cancer cells. In addition, the knockdown of KCNQ1OT1 has been reported to significantly induce the apoptosis of osteosarcoma cells (28) and nonsmall cell lung cancer cells (20), while the silencing of KCNQ1OT1 was shown to impede methotrexate-resistant colorectal cancer cell tumor growth in nude mice (22). In vivo, we discovered that the downregulation of KCNQ1OT1 repressed the volume growth and reduced the weight of the tumors, indicating that KCNQ1OT1 may acts as a carcinogenic and chemo-resistant biomarker for SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…ALDOA is a ubiquitous glycolytic enzyme that drives the glycolytic metabolism pathway in mammalian cells and is mainly expressed in adult muscle tissue. Overexpression of ALDOA has been observed in a variety of cancers including renal clear cell carcinoma [37], lung squamous cell carcinoma [38], colorectal cancer [39], osteosarcoma [40], and oral squamous cells [41], suggesting that glycolysis is enhanced in these cancer cells. However, the current expression of ALDOA in ICC is still unclear, and its regulatory mechanisms involved in tumor progression have yet to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Until 2019, Qin et al found that Itaconate can inhibit ALDOA's enzymatic activity by modifying Cys73 and Cys339 of ALDOA without changing its protein expression level [12]. As an important metabolic enzyme in the glycolytic pathway, ALDOA has been shown to be involved in the regulation of the progression of a variety of tumors [37][38][39][40][41]. Our study also confirmed that the high expression of ALDOA promoted the progress of ICC, and Itaconate can directly inhibit the glycolysis level of ICC tumor cells and thus affect tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence suggested that miR-34c-5p expression was closely associated with a poor prognosis and unfavorable clinicopathological parameters (20,21). Shen et al indicated that the lncRNA KCNQ1 opposite strand/antisense transcript 1 sponged miR-34c-5p to promote osteosarcoma growth via aldolase, fructose-bisphosphate A-enhanced aerobic glycolysis (22). Numerous other studies have revealed that miR-34c-5p was closely related to the development of numerous types of human malignant cancer (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%